Utilization of pea starch and fibre fractions for replacement of wheat crumb in beef burgers. (March 2020) - Pietrasik, Z.; Sigvaldson, M.; Soladoye, O.P.; Gaudette, N.J.
Abstract: Beef burgers (22% fat) were formulated to contain 5% of pea starch (PS), pea fibre (PF) or their combinations (PS:PF; 75:25, 50:50, 25:75). Wheat crumb treatment served as control. Incorporation of pea fractions into burgers did not affect ( P > .05) the colour of fresh burgers or the colour stability over 5 days of storage. All burger treatments containing pea fibre had lower ( P < .05) cook loss than those formulated with wheat crumb or pea starch. Wheat crumb burgers were significantly ( P < .05) softer, less cohesive and chewy than treatments with pea starch and fibre fractions. While panelist feedback suggest that 50:50 blend resulted in optimal firmness and juiciness characteristics, the acceptability mean scores of all pea starch and pea fibre blends were equivalent to wheat crumb control for all attributes which suggests that all combinations of pea starch and fibre can be utilized as gluten free alternatives to wheat crumb for meat binder applications without any detrimental impact on consumer acceptability. Highlights: Pea starch and fibre were utilized for replacement of wheat crumb in beef burgers Colour stability of burgers was not affected by pea starch and fibre fractions Burgers with pea fibre had lower cook loss than those with wheat crumb or pea starch Firmness of cooked burgers increased with increasing incorporation levels of pea fibre 50:50 blend of pea starch and fibre resulted in optimal firmness and juiciness